Reacción de comunidades rurales de la cordillera occidental de Perú en interacciones con el puma (Puma concolor), con y sin pérdida de animales domésticos - Mazzolli, Marcelo (2019)
Records of interactions of pumas with rural communities (n= 7) are registered from 2013 to 2017, four of them with attacks on domestic herds, which resulted in the persecution and death of the puma. In the remaining three records, without damage to domestic herds, the puma was captured, either by the community, or by the public service, and translocated by the public service to a new area. Despite the low sample size, the results revealed: (1) That, there are cases in which the population does not eliminate the feline promptly, but calls for assistance from the authorities; (2) That the authorities react as best they can to carry out translocations - in spite of that, in one occasion a wild puma was sent to a zoo and in other it was killed, which requires the implementation of a standardized protocol to aid decision making in these situations. The results indicate other possible consequences: (1) That the tolerance levels of the population appear to be lower when there are losses of domestic herds; (2) A possible expansion of the puma population, as in other regions of its distribution, due to interactions in residential areas and registry near the desert coast, away from appropriate habitats.